1983
DOI: 10.1111/j.1365-2478.1983.tb01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Migration by Extrapolation of Time‐dependent Boundary Values*

Abstract: MCMECHAN, G.A. 1983, Migration by Extrapolation of Time-Dependent Boundary Values, Geophysical Prospecting 31,413-420. Migration of an observed zero-offset wavefield can be performed as the solution of a boundary value problem in which the data are extrapolated backward in time. This concept is implemented through a finite-difference solution of the two-dimensional acoustic wave equation. All depths are imaged simultaneously at time 0 (the imaging condition), and all dips (right up to vertical) are correctly m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
258
0
3

Year Published

1995
1995
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 754 publications
(261 citation statements)
references
References 10 publications
0
258
0
3
Order By: Relevance
“…As an example, Lerosey et al (3) demonstrated that subwavelength (that is, super-resolution) imaging of the source location could be achieved by refocusing scattered microwave energy from near-field scatterers. They denoted this refocusing operation as a timereversal mirror (4,5), which is similar to reverse time migration by exploration geophysicists (6)(7)(8) except that no velocity model is required because the Green's functions for refocusing are recorded in the data.…”
Section: Introductionmentioning
confidence: 99%
“…As an example, Lerosey et al (3) demonstrated that subwavelength (that is, super-resolution) imaging of the source location could be achieved by refocusing scattered microwave energy from near-field scatterers. They denoted this refocusing operation as a timereversal mirror (4,5), which is similar to reverse time migration by exploration geophysicists (6)(7)(8) except that no velocity model is required because the Green's functions for refocusing are recorded in the data.…”
Section: Introductionmentioning
confidence: 99%
“…The TRI technique in seismology has been used in source location and identification of source mechanisms (Gajewski and Tessmer 2005;Larmat et al 2006Larmat et al , 2010Kawakatsu and Montagner 2008;Steiner and Saenger 2010;Artman et al 2010;Debski 2015). In seismic exploration the TRI technique has been applied to wave field migration (Baysal et al 1983;McMechan 1983;Tarantola 1988;Fichtner et al 2006) and structure imaging in complex geological conditions like salt domes (Willis et al 2006). Most of these projects exploited TRI for an assumed single point source location.…”
Section: Introductionmentioning
confidence: 99%
“…Seismic wavefield modeling is a key component of seismic imaging, e.g., reverse-time migration [3,27,33,49,50,52,53,60], and inversion, e.g., full-waveform inversion [36,37,43,48]. Due to the heterogeneity of the Earth, the simulation of seismic wavefields is achieved most commonly using numerical methods, such as the finite-element method [8,30,35], the finite-difference method [1,25,44,45], spectral-element method [23,24], or discontinuous Galerkin [6,7,11,15,21].…”
Section: Introductionmentioning
confidence: 99%